The effects of cynaroside on lipid metabolism and lipid-related diseases: a mechanistic overview - Cen, Chenyi; Li, Jiahuan; Zhou, Pu; Fisher, David; Hien, Nguyen Thi Thu; Musabaev, Erkin; Pronyuk, Khrystyna; Zhao, Lei (Frontiers in Pharmacology, 2025)
Cynaroside is a natural flavonoid compound, which is widely found in plants. It has the effects of lowering fat, anti-diabetes, anti-inflammatory, antioxidant, anticancer, antibacterial and liver protection. Recent studies have shown that cynaroside regulates fat metabolism through multiple mechanisms, including modulating lipase activity, enhancing gut health and suppressing inflammatory responses. These processes involve the NF-κB, NLRP3 and JAK/STAT inflammatory pathways, and other signaling pathways. By controlling complications associated with abnormal fat metabolism, cynaroside has been demonstrated therapeutic effects on obesity, fatty liver disease, type 2 diabetes and other conditions. Therefore, it shows great potential as an alternative treatment for lipid metabolism-related diseases. However, although the extraction method of cynaroside has been mature, the study of its monomer is still in the initial stage, and there is no complete human efficacy and safety evaluation report. This paper introduces the molecular structure, source and pharmacological action of cynaroside, and systematically reviews the mechanism of regulating lipid metabolism of cynaroside, so as to expand the application value of cynaroside. In addition, it also puts forward the challenges, solutions and future research directions in the clinical application of cynaroside.